『도덕형이상학 정초』에서 선한 의지와 비대칭성 문제 - 강은아; Kang Euna (칸트연구, 2024)
본 논문에서 나는 『도덕형이상학 정초』의 오직 선한 의지만이 무제한적인 가치를 갖는다는 칸트 주장이 어떻게 정당화될 수 있을지를 가치의 비대칭성 반론을 검토함으로써 탐구한다. 첫째로, 나는 무제한적 선의 후보로 칸트가 검토하는 세 후보, 자연적으로 주어진 것, 운으로 주어진 것, 의지는 공통적으로 행위와 관련된 실천적 선을 가진 것으로 본다면 이 분류가 완전하고 건전한 것일 수 있음을 보인다. 둘째로, 세 후보 중에서 의지는 행위자가 자신이 이뤄낸 것이라는 점에서 달리 주어질 수 있다는 점에서 근본적으로 우연적인 나머지 두 후보와 구별되며, 이 점이 선한 의지에 무제한적인 가치를 가질 근거를 제공한다는 점을 논증한다. 결론적으로, 나는 선한 의지와 다른 선한 것들의 가치의 비대칭성의 근저에는 자기가 이룬것과 우연히 주어진 것의 대비가 있음을 밝힌다. 둘은 각기 자신의 선함을 자기와 자연이라는 전혀 다른 원천으로부터 부여받으며, 이 원천의 차이가 가치의 비대칭성의 근거가 된다. 결국, 선한 의지의 무제한적 가치라는 보통 사람의 견해는 자연과 자기라는 대비에 근거해서 정당화된다. In the Groundwork, Kant asserts that good will, and only good will, has unlimited value. In this paper, I examine this assertion by considering the asymmetry of value objection. First, I argue that Kant’s classification of good things―the gifts of nature, the gifts of fortune, and the will―could be a complete and sound division if these candidates are considered practical goods. Second, I argue that the will is fundamentally distinct from the other two as it is not accidental at all, and that the agent has achieved it by himself. Thus, good will deserves special value in this respect. In conclusion, there is a contrast between what one has achieved and what happened to be given at the root of the asymmetry of the value of good will and other good things. Each of the two is endowed with their worth from completely different sources, self and nature, whereas the difference between these sources serves as the basis for the asymmetry of values. After all, the common view of the unlimited value of good will is justified based on the contrast between the nature and self.